Answer:
(x + 6)² + 16 = 0
Explanation:
To complete the square we will first need to get our equation to look like: x² + bx = c
Here we have x² + bx + c = 0 → x² + 12x + 52 = 0
- First we need to subtract our c, in this case 52, from both sides to get x² + 12x = -52
- We then need to add
to both sides of the equation - Here our b value is 12, so plugging this into our formula we get
- Adding 36 to both sides our equation becomes: x² + 12x + 36 = -52 + 36
- Then combining like terms on the right side we get x² + 12x + 36 = -16
- Now making our left side of the equation into a perfect square we get: (x + 6)² = -16
- Finally adding the 16 to both sides of the equation we get: (x + 6)² + 16 = 0